ANALISIS HARGA LAHAN MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS DI KECAMATAN GEDEBAGE KOTA BANDUNG - Muhammad Alghifari Desta (Geography Education Study Program, Universitas Samudra, 2022)
Mapping of land prices in Gedebage District, Bandung City is very much needed, because land price increases occur rapidly as a result of economic growth. Mapping of land prices can be influenced by several factors such as land use, positive land accessibility, and negative land accessibility. The purpose of this research is to analyze the map parameters regarding the estimated land price in Gedebage District, Bandung City. The method used is a qualitative and quantitative approach. The research consisted of several stages, namely preparation, data processing, and data analysis. Research on land prices in Gedebage District produces information on land price estimates which are divided into 5 classes starting from very low to very high. The most influential parameter on land prices is land use. The more strategic a land is, the higher the land price will be.